X-linked Hyper IgM (HIGM1) in an African kindred: the first report from South Africa - Henderson Howard E; Hughes Jane; Eley Brian S; Pienaar Sandra (BMC, 2003)
Abstract Background The objective of this study was to describe the clinical and molecular features of the first South African family with X-linked hyper-IgM syndrome (HIGM1). Methods Diagnoses were based on immunoglobulin results and the absence of CD40 ligand (CD40L) expression on activated T-cells. Complete molecular characterisation involved CD40L cDNA sequencing, and genomic DNA analysis by polymerase chain reaction amplification, restriction enzyme digestion and sequencing. A PCR-based diagnostic assay was established for carrier detection and prenatal diagnosis in this family. Results There were originally six children, three males and three females. The eldest boy died after being diagnosed with hypogammaglobulinaemia, before HIGM1 was considered. This disorder was diagnosed in the second eldest boy at the age of 5 years, after failing to detect CD40L expression on his activated T-cells. A deficiency of CD40L was also confirmed in the youngest male at the age of 5 years. Both younger brothers have since died of infections relating to HIGM1. Molecular investigation showed that exon 3 was deleted from the CD40L mRNA of the affected males. Genomic DNA analysis identified a 1.5 kilobase deletion, spanning exon 3 and including extended flanking intronic sequence. Carrier status in the mother was confirmed by RT-PCR of her CD40L mRNA. Genetic analysis of the three female children was deferred because they were below the legal consenting age of 18 years. A PCR-based assay for genomic DNA was established for easy identification of female carriers and affected males in the future. Conclusions This study confirmed the diagnosis of HIGM1 in the first South African family to be investigated and identified a novel mutation in the CD40L gene.